Synthesis of colorless polyimides with high Tg and low coefficient of thermal expansion from benzimidazole diamine containing biamide. Issue 9 (4th March 2023) - Li, Dongwu; Li, Dandan; Ke, Zhao; Gu, Qian; Xu, Ke; Chen, Chunhai; Qian, Guangtao; Liu, Gang
Abstract: Colorless polyimides (CPIs) with superheat resistance and low coefficient of thermal expansion (CTE) are required urgently to employ as plastic substrates in flexible‐display devices. To attain the target properties, 2‐(2‐methyl‐4‐(4‐aminobenzamido)phenyl)‐5‐(4‐aminobenzamido)‐ N ‐phenylbenzimidazol (AB‐MPBZ) that contains biamide was synthesized, and its homo‐ and co‐polyimides were prepared with 1, 2, 4, 5‐cyclohexanetetracarboxylic dianhydride (HPMDA) and cyclobutane‐1, 2, 3, 4‐tetracarboxylic dianhydride (CBDA). The crank‐shaft‐like amide groups effectively increases the linearity and stiffness of polymer segments, providing CPI films with low CTE. On the basis, the CBDA based poly(benzimidazole imide) (PBII) series with dense interchain packing exhibits further reduced CTE down to 22 ppm K −1 and increased glass‐transition temperature ( T g ) up to 404 °C. Such good thermal properties indicate that the resultant copolyimides have potential applications as colorless flexible substrates. These provide a feasible approach to balance thermal and optical performance of polyimides. Abstract :